2022
DOI: 10.1093/eurheartj/ehac544.1324
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of NT-proBNP following high-risk myocardial infarction in the PARADISE-MI Trial

Abstract: Background/Introduction N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a marker of ventricular wall stress and a potent predictor of death and heart failure (HF) across multiple populations (from healthy insurance applicants to various disease entities). Purpose To evaluate the prognostic importance of NT-proBNP in patients with acute myocardial infarction (AMI) complicated by left ventricular systolic dysfunction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Clinically, the adverse reactions with a higher incidence of ARNI and ACEI/ARB include hypotension, hyperkalemia, angioedema, cough, and liver and kidney dysfunction. in this study, 7 papers (14,18,19,22,24,27,28) described the incidence of hypotension (P < 0.00001, I 2 = 0%), 4 papers (14,18,22,27) described the incidence of hyperkalemia (P = 0.60, I 2 = 7%), 4 articles (14,18,19,27) describe the incidence of angioedema (P = 0.33, I 2 = 10%), 5 articles (14,18,22,27,28) describe the incidence of renal insufficiency (P = 0.94, I 2 = 0%), and 3 articles (14,22,24) described the incidence of cough (P < 0.00001, I 2 = 0%), and the incidence of overall adverse reactions was not statistically different (P = 0.16, I 2 = 71%). Subgroup analysis showed that the heterogeneity of the total adverse event rate was derived from different clinical symptoms, and the homogeneity among subgroups was good.…”
Section: Adverse Eventsmentioning
confidence: 58%
See 4 more Smart Citations
“…Clinically, the adverse reactions with a higher incidence of ARNI and ACEI/ARB include hypotension, hyperkalemia, angioedema, cough, and liver and kidney dysfunction. in this study, 7 papers (14,18,19,22,24,27,28) described the incidence of hypotension (P < 0.00001, I 2 = 0%), 4 papers (14,18,22,27) described the incidence of hyperkalemia (P = 0.60, I 2 = 7%), 4 articles (14,18,19,27) describe the incidence of angioedema (P = 0.33, I 2 = 10%), 5 articles (14,18,22,27,28) describe the incidence of renal insufficiency (P = 0.94, I 2 = 0%), and 3 articles (14,22,24) described the incidence of cough (P < 0.00001, I 2 = 0%), and the incidence of overall adverse reactions was not statistically different (P = 0.16, I 2 = 71%). Subgroup analysis showed that the heterogeneity of the total adverse event rate was derived from different clinical symptoms, and the homogeneity among subgroups was good.…”
Section: Adverse Eventsmentioning
confidence: 58%
“…The quality of the included studies was relatively high. Of these, three studies were assigned at the discretion of the clinician (18,19,28), two studies used an interactive web for grouping and assignment concealment (14,21), and two studies used sealed envelopes for randomization and assignment concealment (15, 20), three studies used random number tables for randomization (25,26,29). The remaining studies mentioned randomization but did not mention the specific method and did not mention allocation concealment in the text.…”
Section: Risk Of Bias In the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations